1986 et ses problèmes en assurance - Laberge, Gérald (Assurances)

(untitled) (HEC Montréal, 1987)
In a speech to the Amos Chamber of Commerce, Mr. Gérald Laberge exposed the problems the insurance market must face. He agreed with the fact that, at first sight, certain explanations are difficult to grasp if one is unaware of the facts. The problems the market must contend with may be traced to fierce competition which, during the three or four years preceding the upward adjustments and premiums implemented from late 1985 to today, have resulted in substantial reductions in premiums, while the situation went from bad to worse. The decrease in rates no longer reflected the situation and monetary inflation, legal inflation, certain lenghty suits coupled with such factors as the rise in interest rates and legal costs and the increasingly generous treatment of victims by courts made matters worse. Mr. Laberge cites several cases where premiums, even when increased substantially, were comparable to their level before the wave of unjustified premium reductions swept in.